Comparative Supply Chain Risk Management in ASEAN and European Manufacturing: A Structured Literature Analysis - Kimberly Febrina kodrat; Hasan Sitorus (JTI: Jurnal Teknik Industri, 2026)
Supply chain risk management (SCRM) has become a critical strategic imperative in the post-pandemic and geopolitically turbulent era, yet systematic comparative evidence across ASEAN and European manufacturing contexts remains scarce. This paper employs a Structured Literature Analysis (SLA) of 50 peer-reviewed studies published between 2008 and 2025 to comparatively examine SCRM frameworks, risk typologies, mitigation strategies, digital transformation trajectories, and sustainability integration across the two regions. To the best of the authors’ knowledge, this is the first study to apply a thematic cross-regional comparison framework specifically to ASEAN European manufacturing SCRM divergence, addressing a gap left by predominantly single-region studies. Key findings reveal that both regions face structurally similar risk categories geopolitical disruption, demand volatility, natural disasters, and supplier concentration but adopt divergent strategic responses: ASEAN systems prioritize network-based resilience and regional value chain integration, while European manufacturers increasingly pursue strategic autonomy and regulatory-driven resilience. Digital transformation and sustainability serve as important resilience enablers across both contexts, though their implementation depth and regulatory drivers differ substantially. Theoretical contributions include a Cross-Regional SCRM Divergence Model (CR-SCRM) and a risk-resilience-sustainability integration framework with implications for policymakers and operations managers. Keywords: Supply Chain Risk Management; ASEAN; European Manufacturing; Resilience; Digital Transformation; Sustainability; Geopolitical Risk; Comparative Analysis